Pengaruh Shopping Enjoyment, Pengalaman Pembelian dan Religiusitas Terhadap Minat Beli Produk Fashion Di Online Shop (Studi Pada Generasi Z di Kota Jambi) - Elza Berta Salsabila; Agustina Mutia; Syahril Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Someone's urge to buy anything develops after being stimulated by the object he sees. This desire first develops into a desire to test the product, then develops into a desire to buy in order to have it. The formation of purchase intention is influenced by several factors, one of which is shopping enjoyment, purchasing experience and religiosity. This study aims to determine the effect of shopping enjoyment, purchasing experience and religiosity on consumer buying interest in fashion products in online shops. Samples were taken as many as 270 respondents using the sampling method in this study, namely Proportionate Stratified Random Sampling. This study used the SPSS calculator version 22. The results showed that shopping enjoyment, buying experience, and religiosity had a positive and significant effect on the intention to buy fashion products in online shops. Based on data analysis in this study, these variables are valid and reliable